2011
DOI: 10.3109/10903127.2011.615008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Emergency Medical Services Scope of Practice for Acute Cardiovascular Events

Abstract: We noted statistically significant variations in scope of practice by rural vs. urban setting, medical director involvement, and type of EMS service (fire department-based/non-fire department-based; volunteer/paid). These variations highlight local differences in the composition and capacity of EMS providers and offer important information for the transition towards the implementation of a national scope of practice model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
2
9
1
Order By: Relevance
“…Although low patient volume and rural locations are reported to limit EMS stroke care capacity (7,2225), our comparisons by patient volume and county population density did not demonstrate strong variation by these characteristics. In fact, our findings show that some systems with low patient volume in rural areas have high stroke care capacity.…”
Section: Discussioncontrasting
confidence: 53%
“…Although low patient volume and rural locations are reported to limit EMS stroke care capacity (7,2225), our comparisons by patient volume and county population density did not demonstrate strong variation by these characteristics. In fact, our findings show that some systems with low patient volume in rural areas have high stroke care capacity.…”
Section: Discussioncontrasting
confidence: 53%
“…A survey of EMS practices in 9 states showed that only personnel with paramedic credentials were authorized to perform an ECG in 88% of agencies while only 23% and 37% of agencies authorized ECG performance at the EMT basic and intermediate level of licensure, respectively. 14 Although fewer than 10% of chest pain patients in our study were transported without at least 1 member of their team having paramedic certification, gaps in certification were greatest in rural areas. The 2009 EMS protocol in North Carolina authorized individuals who hold an EMT‐basic certification or above to perform an ECG.…”
Section: Discussionmentioning
confidence: 73%
“…[12][13][14] The practice environments for EMTs and paramedics differ, with paramedics responsible for critical tasks such as advanced airway management of critical patients and termination of resuscitation in the field at many agencies. 34 These differences appear to impact the stress levels, burnout, and other physical and mental health conditions of EMS professionals, with paramedics reporting higher levels of these negative factors. [12][13][14] These factors may result in poorer health behaviors and thus poor CVH.…”
Section: Discussionmentioning
confidence: 99%
“…In the EMS setting, measuring blood pressure in patients and potentially one's self is a common task, whereas point-of-care testing for cholesterol and fasting blood glucose is more limited. 34 The factors of blood glucose and cholesterol were excluded from the CVH score calculated, and based on the sensitivity analysis using the complete observations with data on all seven components, the risk of misclassification or bias introduced was likely low with no change in direction of association from the main analysis. Non-response bias was also a concern due to the low response rate from the electronic survey.…”
Section: Limitationsmentioning
confidence: 99%